Reliability Measurements of the Furniture Frames with Selected Joint Types - Uysal, Mesut (North Carolina State Univ Dept Wood & Paper Sci, 2024)
The reliability was evaluated for frame construction with mortise and tenon (MT), dowel, and non-glued and glued staple joints made of beech wood. The moment capacities of the T-shaped joints were determined under static vertical loads. The MT joint had an average moment capacity of 204 Nm, followed by dowel joints (154 Nm). In staple joints, joint strength increased after gluing. A three-seat sofa frame was defined and theoretically subjected to loads on arm rails, side rails, and back posts. Moment levels on the joint of the frame were obtained by using the stiffness method. To measure the reliability, these moment levels were assumed to be normally distributed with a coefficient of variation of 10%; accordingly, the normal distribution of the data sets was transformed into a normal standard distribution, and then, the reliability of each joint on the frame was obtained by using probabilistic approaches. MT joints were found to have the highest moment capacity and, correspondingly, the highest reliability (99.99%). Gluing the staple joints increased the strength, so their reliabilities were increased. In designing frame construction, the critical joints should be determined, and then, the joinery system with the higher reliability should be used.
Keywords: Reliability; Probabilistic approach; Mortise and tenon joints; Dowel joints; Staple joints; Normalizing; Multiple failure modes; Parallel system